Pengaruh Proses Rekrutmen Proses Seleksi dan Kompetensi Karyawan terhadap Kinerja Karyawan pada Bank Kaltim Samarinda - Freddy Tumbuan Pasaribu; Yonathan Pongtuluran; Doddy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This research aim to analyze the influence of recruitmen selection process and competence of employees on employee performance by using multiple regression analyze. Population in this research were  employees with  a population  using methods accidental in the  research 57  respondents.  The hypotesis  of  this  research  indicate  that  the  recruitmen  process  variable  selection  process  and competencies  of  employees  simultaneously  positive  and  significant  effect  in  the  perfomance  of employees at Bank Kaltim Samarinda. The calculation result standardized coefficients indicate more dominant recruitmen process variable effect the performance of employees samarinda.R and R Square result show that the level of relations with the variabel employee performance is moderate.Keyword:   Influence  the  Process  of  Recruitmen  Selection  Process  and  Competencies  to Employee Performance